Study of Flood Vulnerability in Pesanggrahan District, South Jakarta - Herika Muhamad Taki; Anita Sitawati Wartaman (Politeknik Negeri Batam, 2022)
Pesanggrahan Sub-district is located in South Jakarta Administrative City, DKI Jakarta Province, Pesanggrahan Sub-district is crossed by Pesanggrahan River which divides sub-districts and crosses several villages that are included in Pesanggrahan District. In the rainy season, floods often occur due to overflowing water in this Pesanggrahan river and resulting in material and non-material losses. The purpose of this study is to determine the level of flood vulnerability that has occurred, especially in areas that have not been affected in order to avoid the risks that occur. The benefit of this research is to input mitigation efforts that will be carried out in the event of a flood. The research variables used in this study are the area of ​​the flood range from the river, elevation, slope and land use. The research method is using GIS technique to superimpose or map overlay, scoring, and weight using Geographic Information System (GIS) software. The expected result is the creation of a classification of the level of flood vulnerability and its extent. The planned mitigation directives are directives related to river body improvement, utilization of river commensurate space intended for the government, and the community. This research is one of the personal research roadmaps and is in accordance with the faculty research roadmap. This research is included in the building and environmental disaster mitigation research cluster, the leading field of green urban environment and the national research master plan on disaster management. The planned output is scientific work published in reputable international journals and Intellectual Property Rights.